Gender-segregated analysis of the poultry value chain in Ghana. (4th May 2019) - Mensah-Bonsu, Akwasi; Lartey, Nancy N.; Kuwornu, John K. M.
Abstract: This study examined the poultry value chain in the Dormaa District and Sunyani Municipality in the Brong-Ahafo Region of Ghana. A multi-stage sampling procedure was used to obtain cross-sectional data from 203 value chain actors through the administration of a structured questionnaire. The poultry products considered were broilers and layers, and the value chain actors were producers, traders, and processors. The results of the Duncan's Index of Dissimilarity of ∼75% revealed that the poultry value chains are highly gender-segregated (i.e., men and women cluster at different levels of the value chain). The producer level of the value chain was dominated by men, and the trader and processor levels were dominated by women. The results regarding value addition and return on investment (ROI) revealed that the producers added the highest value in both the broiler and layer value chains. The producers' ROI was generally higher in the broiler value chain than in the layer value chain. The male value chain actors were found to add higher value compared to their female counterparts. This was because the men generally operated on larger scales than the women. The study highlights the role of the government, researchers, nutritionists and training institutions for the development of the poultry value chain.